Statistical authoritarianism: The government's strategy to control the media through data manipulation and digital transparency solutions - Muhammad Fikri; Haura Mudya Maysha; Abd. Rahman (Tamalanrea: Journal of Government and Development (JGD), 2026)
The rapid expansion of digital technology has transformed the relationship between the state, media, and society. Beyond facilitating communication and information exchange, digital infrastructure increasingly functions as a strategic arena for shaping public narratives and political legitimacy. This study examines how data and statistics can be utilized as instruments of information control within the digital media ecosystem and explores their implications for democratic governance. Using a qualitative approach through a Systematic Literature Review (SLR), this study analyzes scholarly works on digital authoritarianism, media control, data governance, disinformation, and political communication published between 2019 and 2025. The analysis reveals that contemporary information control extends beyond censorship and digital surveillance to include the strategic selection, framing, and presentation of statistical data. In this context, public data can influence how citizens interpret social realities and evaluate government performance. Based on these findings, this study develops the concept of statistical authoritarianism, which refers to the use of data and statistics as instruments for constructing political legitimacy and shaping public perception without relying on overt repression. The study contributes to the literature by distinguishing statistical authoritarianism from digital authoritarianism and disinformation while highlighting the growing significance of data-driven power in contemporary digital societies.